Sorption Study of Methyl Orange on the Iraqi Kaolinite Clay - Al-Ma'amar, Ali A (Al-Nahrain Journal of Science, 2018)
The sorption of methyl orange on the kaolinite clay was studied thermodynamically and kinetically, the sorption was of Freundlich type and the multi-layers were formed, and the sorption was a combination of adsorption and absorption, but in some cases the desorption was occurred. The Freundlich constants were calculated to specify the sorption capacity, and sorption intensity. The calculation of thermodynamic parameters revealed that the process was exothermic, ordered, and non-spontaneous at the temperature range(298-328K). Three kinetic models were exploited to calculate the rate constant, diffusion constant, rate of adsorption, and desorption parameter.